Alih Teknologi Administrasi Rusun Kota Pontianak Berbasis Laravel - Dzulqarnain, Muhammad Faqih; Khelfa Arzakky Syukri; Tegar Adji Nugroho (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The current administration system for apartment buildings in Pontianak city still relies on manual data recording methods, which tend to cause various recording errors such as delays in data processing, incorrect data entry, and difficulties in accessing information. This condition has an impact on suboptimal service to apartment residents. As an alternative to address this problem, it is proposed to develop a web-based information system that can digitize data from various business processes in apartment management. This system is designed using the Laravel framework, a popular framework for web application development. The stages in this community service include in-depth analysis of system requirements that are suitable for the conditions of apartment buildings in Pontianak city, designing a user-friendly and efficient system, building the system based on the design that has been created from manual form recording, and conducting training for apartment managers to be able to operate the system well. This technology transfer has a positive impact on the change in the administration model and it is expected to create more effective and efficient apartment management and is easily accessible because it is online. Some other benefits that occur include increased accuracy of resident data, ease of accessing information, data transparency, and improved service quality for residents